Definição de plano de melhorias de desempenho da Unidade de Hidrogênio da planta de cloro-soda de Aratu e avaliação de viabilidade econômica - FERREIRA, Tatiana de Freitas (2016)
The chlorine production process through brine electrolysis, using diaphragm cells, results in a byproduct production of hydrogen gas. This stream is washed, cooled and compressed before it is sent to consumers: boilers that use hydrogen as a complementary fuel for steam generation and chloridric acid burner, where hydrogen is used to react with chlorine to generate chloridric acid 32% solution (mass percentage). Part of hydrogen production at electrolysis series is released to atmosphere due to poor efficiency and low design capacity for hydrogen area equipment. The main objective of this study is to identify the capacity restrictions and proposes performance improvement actions to eliminate the hydrogen production losses to atmosphere. Initially, it was evaluated the measurement system and it was developed the mass and energy balance and defined the model premises. The data collection was performed, the premises were checked and the uncertainty measurements were evaluated. The Aspen simulation was built and a physical properties model was selected and checked with experimental data. The data collected were used to feed and validate the simulation. The proposed model was able to describe the process and it was used to evaluate strategies to increase hydrogen unity utilization. The investments needed to maximize the hydrogen utilization are detailed at a technology and maintenance plan, with an economic viability analysis. After some options evaluation, it was recommended an investment route where initially main equipment will be recovered, cooling tower and washing and cooling column. Later, it is proposed an evaluation for compressor change, bringing more operational flexibility. Projects implementation will result financial savings regarding to an increase of hydrogen utilization at boilers replacing other fuels.